A Hybrid-ARQ Method with Adaptive Receiving Buffer Duration in Real Time Video Streaming. Issue 1 (1st April 2022) - Cheng, Baoping; Tao, Xiaoming; Lei, Peng; Zhou, Junhua; Wang, Duo; Chen, Min
Abstract: To decrease end-to-end delay for streaming media over internet, the transmission method based on best-effort model is always employed in Real Time Communication (RTC) system. However, the packet-loss, jitter and congestion occur frequently because the quality of transmission cannot be guaranteed, which causes lag and splash of video. Therefore, an optimized hybrid Automatic Repeat Query (ARQ) solution with adaptive receiving buffer duration is proposed to guarantee the quality of video transmission. In the method, the loss rate was used to adjust the buffer duration and calculate the redundancy for Forward Error Correction (FEC). The results show that the method in this paper gains lower end-to-end delay and better Mean Opinion Score (MOS) values while ensuring higher fluency in weak network scenarios.